A facile approach for thermal and reduction dual-responsive prodrug nanogels for intracellular doxorubicin delivery. Issue 47 (14th November 2016) - Peng, Huan; Huang, Xiaobin; Oppermann, Alex; Melle, Andrea; Weger, Lindsey; Karperien, Marcel; Wöll, Dominik; Pich, Andrij
Abstract : Temperature and redox dual responsive prodrug nanogels for controlled drug release. Abstract : In this study, thermal and redox dual sensitive nanogels based on N -vinylcaprolactam (VCL) and N -succinimidyl methacrylate (Suma) crosslinked with diallyl disulfide were synthesized via a facile and straightforward method. The reactive succinimide groups were mainly located in the nanogel shell which increases considerably their accessibility for conjugation reactions. Doxorubicin (DOX) was successfully loaded into the nanogel through two different routes. Approximately 91.3% of DOX molecules were covalently bound to the nanogel network via coupling with succinimide groups under mild conditions to obtain prodrug nanogels, while 8.7% of DOX molecules were captured into the nanogels via electrostatic interactions with the –COOH group from the hydrolyzed ester groups of the nanogels. The DOX-loaded nanogels demonstrated volume phase transition temperature (VPTT) near human physiological temperature. The nanogels shrink near body temperature, which could help lock the drug molecules stably in blood circulation. The conjugation of DOX molecules in nanogels avoided premature unspecific drug release under physiological conditions. The small amount of physically loaded DOX (due to electrostatic interactions) could be partially released as free DOX due to the increasing acidic conditions in the endosome/lysosome pathway. The chemically conjugated DOX was released in the form of a prodrug polymer triggered by the high concentration of glutathione in the cytosol that induced nanogel degradation. The present drug delivery system exhibits a sustainable delivery profile in the intracellular release study and high antitumor activity. We are convinced that the thermal and reduction dual-responsive prodrug nanogels have tremendous potential in controlled drug release.